Vinaññʻʺ dhamma kaṃ cī raṅʻ thuṃʺ myāʺ - Kraññʻ Phe, Ūʺ (Naññʻʺ sacʻ Cā ʼupʻ Tuikʻ : Ne Laṅʻʺ Piṭakatʻ Cā pe Phranʻʹ khyī reʺ Ṭhāna, 1982)
One hundred years of rulings of the monastic courts in Burma, 1853-1953, applying Vinayapitaka, Buddhist canonical text for monastic rules.